(untitled) (Journal of Applied Oral Science, 2015)
Objectives Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disease. Cytokines play an important role in the pathogenesis and disease progression of OLP. Various reports have implicated cytokine gene polymorphisms in susceptibility to develop some immune mediated conditions including OLP. The purpose of this study was to investigate the association of tumor necrosis factor (TNF)-α, TNF-β and interleukin (IL)-10 gene polymorphisms with the OLP risk. Material and Methods Forty two unrelated patients with OLP and 211 healthy volunteers were genotyped for TNF-α (-308 G/A), TNF-β (+252A/G), IL-10 (-1082G/A), IL-10 (-819C/T), and IL-10 (-592C/A) polymorphisms. Results The frequencies of allele A and genotype GA of TNF-α (-308G/A) were significantly higher while allele G and GG genotypes were lower in OLP patients as compared to the controls (P;0.05). However, haplotype ATA extracted from 1082G/A, -819C/T, -592C/A polymorphisms of IL-10 were more prevalent in OLP patients when compared to controls indicating its possible association with OLP susceptibility. Conclusion It is concluded that TNF-α (-308G/A), TNF-β (+252A/G) and IL-10 (-1082G/A, -819C/T and -592C/A) polymorphisms are associated with the susceptibility of OLP, thus giving additional support for the genetic basis of this disease.